PENERAPAN TEKNOLOGI TEPAT GUNA: INOVASI ALAT PENABUR BIBIT JAGUNG UNTUK MENINGKATKAN EFISIENSI TANAM - Neli Rahnatul Izzah; Haura Iza Faizah; Irene Avianti Putri; Ahmad Jimli Zidan; Muhammad Afril Lusdianto; Angga Dutahatmaja (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Maize farming is one of the important sectors in national food security. However, maize farmers in Petak Village, Pacet Subdistrict, Mojokerto Regency still face obstacles in the seed planting process, which is still done manually with the traditional tugal system. This method takes a long time, requires a lot of labor, and results in inconsistent spacing that affects productivity. This community service activity aims to apply appropriate technology in the form of a semi-automatic corn seed sowing tool that can increase time and labor efficiency in the planting process. This tool is designed with a simple mechanical system that can adjust the planting distance consistently, reduce planting time by 60% and can reduce labor costs by 40%, so that it can be operated by one person (farmer). The results of the activity show that the corn seed sowing tool can increase the efficiency of planting from what was originally manual and done only one by one.